Hierarchical core-shell Ni-Co-Cu-Pd alloys for efficient formic acid oxidation reaction with high mass activity - Kim, So Jung; Choi, Seunggun; Kim, Kang Min; Ali, Ghulam; Mhin, Sungwook; Enkhtuvshina, Enkhbayar; Jung, Sun Young; Thao, Nguyen Thi Thu; Akbar, Muhammad; Chung, Kyung Yoon; Kang, Sukhyun; Song, Taeseup; et al. (Elsevier BV, 2022)
Development of efficient electrocatalyst with a small use of noble metals for formic acid oxidation reaction (FAOR) is the most urgent need in realizing practical direct formic acid fuel cells (DFAFC). Herein, we developed quaternary Ni-Co-Cu-Pd (NCCP) alloys with an intriguing nanostructure, that is, hierarchical core-shell structure, which demonstrates excellent catalytic performance for FAOR with a high mass activity. The mass activity of NCCP for FAOR is 3 folds higher than the benchmark Palladium on Carbon (Pd/C, 10 wt%) catalyst. We reason this exceptionally high mass activity of NCCP to the synergetic effects between the surface decorated Pd nanoclusters and the transition metal cores, resulting in highly disturbed electronic configurations at the surface. In addition, the intriguing nanostructure evolved during FAOR can facilitate atomic, ionic, and molecular transfers during FAOR. The NCCP also demonstrates a high electrocatalytic stability for FAOR, which highlights its potential use for the practical DFAFC.